2017
DOI: 10.18632/oncotarget.16872
|View full text |Cite
|
Sign up to set email alerts
|

The synthetic antihyperlipidemic drug potassium piperate selectively kills breast cancer cells through inhibiting G1-S-phase transition and inducing apoptosis

Abstract: Piper longum L. is a well-known traditional antihyperlipidemic medicine in China, containing medicinal constituents of piperine, pipernonaline and piperlonguminine in its fruit. However, the antitumor properties of these constituents have not yet been studied. We found that potassium piperate (GBK), a derivative of piperine, inhibited proliferation of cancer cells. GBK selectively inhibited the G1-S-phase transition in breast cancer cells and the G1 arrest was correlated with induction of p27 expression, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It was indicated that the major mechanisms for silencing miR-31 in TNBC is hypermethylation of the CpG island of the LOC554202 promoter region [24]. We demonstrated previously that the transcription of DNA methyltransferases DNMT1, DNMT3A, DNMT3B and COQ3 genes were downregulated in GBK-treated MCF-7 cells [28]. In this study, we found that the methylation levels at CpG of lncRNA LOC554202 decreased signi cantly under GBK treatment in a dose-dependent manner in breast cancer cell lines, indicating that GBK treatment affects the epigenetic modi cation at CpG sites by downregulating DNA methyltransferases, and plays an important role in upregulating of both the LOC554202 and miR-31 genes (Figure .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It was indicated that the major mechanisms for silencing miR-31 in TNBC is hypermethylation of the CpG island of the LOC554202 promoter region [24]. We demonstrated previously that the transcription of DNA methyltransferases DNMT1, DNMT3A, DNMT3B and COQ3 genes were downregulated in GBK-treated MCF-7 cells [28]. In this study, we found that the methylation levels at CpG of lncRNA LOC554202 decreased signi cantly under GBK treatment in a dose-dependent manner in breast cancer cell lines, indicating that GBK treatment affects the epigenetic modi cation at CpG sites by downregulating DNA methyltransferases, and plays an important role in upregulating of both the LOC554202 and miR-31 genes (Figure .…”
Section: Discussionmentioning
confidence: 78%
“…The chemotherapy drugs cisplatin (DDP) and Vepeside (VP-16) are widely used as rst-line therapy for metastatic breast cancer and small cell lung cancer [26,27]. In the precious study, we demonstrated that GBK has speci c inhibitory effect on breast cancer cells compared with normal breast cells and other types of cancer cells [28]. In this preclinical study, we want to evaluate the effect of GBK in combination with DDP/VP-16 as agents in breast cancer cells.…”
Section: Combination Treatment With Gbk and Ddp/vp-16 Has Synergisticmentioning
confidence: 99%
“…The chemotherapy drugs cisplatin (DDP) and Vepeside (VP-16) are widely used as first-line therapy for metastatic breast cancer and small cell lung cancer 29 , 30 ). In our previous study, we demonstrated that GBK exerted specific inhibitory effects on breast cancer cells but not on normal breast cells or cancer cell types ( 31 ). In this preclinical study, we want to evaluate the effect of GBK when used in combination with DDP/VP-16 to treat breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies in glioblastoma and breast cancer cells have reported that extracts or active compounds isolated from Piper genus possess anti-tumoural/pro-apoptotic properties [52,53,54,55,56,57,58,59,60,61]. In order to assess whether the compounds we isolated could be developed further for therapeutic applications, we tested their cytotoxic action in the human cancer cells, U373 (glioblastoma astrocytoma) and MCF7 (breast adenocarcinoma) cell lines, since they are widely used as suitable in vitro models of cancer research.…”
Section: Resultsmentioning
confidence: 99%